Experimental Analysis of Absolute Phase Noise of a Harmonically Mode-Locked Semiconductor Laser - Ozharar, S.; Ozdur, I. (Natl Inst Optoelectronics, 2018)
In this work, we have designed and experimentally characterized the absolute phase noise of a fiber coupled semiconductor ring laser at 1550 nm, actively mode-locked at 10 GHz by an external RF oscillator. The dependency of mode-locked laser phase noise to the external RF oscillator phase noise and laser cavity length is investigated using different RF sources and cavity lengths. A timing jitter of 14.6 fs (1 kHz to 1 MHz) has been measured at 10 GHz with a total cavity length of 315 meters.
Ozdur, Ibrahim/0000-0001-6452-0804
Keywords: Mode-Locked Laser; Phase Noise; Semiconductor Laser